Penafsiran Wahbah al-Zuhaili terhadap Isu LGBT dalam Al-Qur’an: Perspektif dan Respon Masyarakat Patani, Thailand - Kanong, Mr. Sahidan (UIN Syarif Hidayatullah Jakarta, 2023)
This research aims to find out Wahbah Al-Zuhaili's interpretation of LGBT verses and find out how the Patani community in Thailand responds to LGBT. This research is included in qualitative research with a library search and field study approach. This research method includes qualitative analysis of the writings of Wahbah Al-Zuhaili, a famous scholar, to understand his perspective on LGBT in the Islamic context. In addition, this research also involves collecting empirical data through interviews, observations, and documentary studies to understand how the Patani community responds to LGBT issues. The results of the analysis show that Wahbah Al-Zuhaili's interpretation of LGBT verses in the Qur'an emphasizes the importance of context, ethics and social norms. Wahbah Al-Zuhaili also said that LGBT behavior is truly stupid, has a bad impact on oneself and others and is strictly prohibited by religion. As for the response of the Patani community regarding LGBT. The response of the Patani community regarding whether LGBT perpetrators should be shunned or not, 18% said they should not be shunned, while 7.2% said they were doubtful and 74.8% said they should be shunned.